Examination of the AAOIFI pronouncement on Sukuk Issuance and its implication on the Future Sukuk structure in the islamic capital market in Malaysia. - Mohammed Idris, Umar; Lahsasna, Ahcene (IIUM Press, 2011)
The Shariah compliant bond defined as "sukuk" has become one of the most dynamic tools for capital mobilization in both the Islamic and conventional capital markets. ItseQ' rapid growth and development has proved it to be a viable tool for raising capital in the international capital markets through Islamically acceptable structures. By the end of2007, the total issues value was estimated at USS35 billion. However, the recent AAOIFI pronouncement on sukuk has created some fear among the investment sectors as well as the sukuk industry. The AAOIFI preannouncement has resulted in the existence of additional standards that have to be observed by the issuers in order to comply with the Shariah rules and regulations. This has somehow slowed down the growth of the instrument in the first quarter of the year 20 II. Although the pronouncement has some impacts and implications on the sukuk industry. there is still an optimism of things gelling better as it moved further. According to some of the statistics, sukuk issuance in the GCC region has increased by 17%, last year to US$I7 billion, which is 30% more than conventional paper debt. In this context, the paper is trying to examine the AAOIFI pronouncement on the shariah compliance issues ofsukuk structuring, its impacts and implications on the future issues